Remote recruiting and video-interviewing older people: a research note on a qualitative case study carried out in the first Covid-19 Red Zone in Europe. Issue 4 (4th July 2022) - Melis, Giulia; Sala, Emanuela; Zaccaria, Daniele
ABSTRACT: There is an urgent need to understand the consequences of the Covid-19 pandemics on older people's lives. However, conducting qualitative research is challenging, because of the shortage of guidelines and methodological research on how to recruit and interview participants during biological disasters, such as pandemics. This paper documents the procedures we adopted to recruit and interview 40 older people living in a rural area of Northern Italy that was subject to the first full lockdown in Europe. Despite the challenges arising when qualitatively researching the old age population in pandemic times, our study has shown that it is feasible to recruit and interview older people remotely. Specifically, community engagement and tailoring video-interviews according to older people's needs and ICT skills are the key aspects to consider when designing these types of studies.